Blinatumomab in the Treatment of Acute Lymphoblastic Leukemia: Russian Multicenter Clinical Trial - SN Bondarenko; EN Parovichnikova; AA Maschan; OYu Baranova; TV Shelekhova; VA Doronin; VYa Mel’nichenko; KD Kaplanov; OS Uspenskaya; AN Sokolov; NV Myakova; IS Moiseev; et al. (Клиническая онкогематология)

(untitled)
Background. Recent advances in the treatment of relapsed/refractory acute lymphoblastic leukemia (R/R ALL) are attributed to the implementation of immunotherapy methods which include blinatumomab, the bispecific engager of a patient’s endogenous T-cells (Blincyto™, Amgen®) (BC).